Application of The TSLS Method in a Simultaneous Equation Model of Investment and Economic Growth Panel Data - Sari, Shafira Niken; Susilowati, Indah (Trunojoyo University of Madura, 2024)
The Indonesian government believes that by increasing investment, it will also be able to encourage economic activity in the country and economic growth will increase. Indonesia's economic growth is not only influenced by investment, but is also supported by the foreign trade sector, namely exports and imports. The purpose of this study is to determine the simultaneous relationship between investment and economic growth as proven through the Hausman test. The test results in a residual probability of 0.000 which is less than the 5% significance level. The results explain that there is a simultaneous relationship between investment and national income which is described by the value of GDP, so that the 2SLS method can be used to determine the factors that influence the two variables.